2010
DOI: 10.1186/1752-0509-4-54
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Control of the Central Carbon Metabolism in Hepatoma Cells

Abstract: BackgroundThe liver plays a major role in metabolism and performs a number of vital functions in the body. Therefore, the determination of hepatic metabolite dynamics and the analysis of the control of the respective biochemical pathways are of great pharmacological and medical importance. Extra- and intracellular time-series data from stimulus-response experiments are gaining in importance in the identification of in vivo metabolite dynamics, while dynamic network models are excellent tools for analyzing comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 80 publications
1
36
0
2
Order By: Relevance
“…Beard and Qian (2005) investigated the impairment of hepatic glucose production in von Gierke’s and Hers’ diseases. Maier et al (2010) analyzed the control of glycolysis in HepG2 cells under conditions of glucose deprivation by fitting a kinetic model to the measured concentrations of 25 extra- and intracellular intermediates. A kinetic model of ammonia detoxification in the liver lobule was constructed by Ohno et al (2008) which accounts for the strict zonation of this metabolic function.…”
Section: Use Of In Vitro Systems For Predicting Liver Toxicitymentioning
confidence: 99%
“…Beard and Qian (2005) investigated the impairment of hepatic glucose production in von Gierke’s and Hers’ diseases. Maier et al (2010) analyzed the control of glycolysis in HepG2 cells under conditions of glucose deprivation by fitting a kinetic model to the measured concentrations of 25 extra- and intracellular intermediates. A kinetic model of ammonia detoxification in the liver lobule was constructed by Ohno et al (2008) which accounts for the strict zonation of this metabolic function.…”
Section: Use Of In Vitro Systems For Predicting Liver Toxicitymentioning
confidence: 99%
“…From this most simple example it is obvious that neither metabolome nor fluxome measurement alone provide full kinetic description that is necessary to make predictions about rate controlling steps, e.g., carrying out a metabolic control analysis,20 or about regulatory characteristics of the network. Only variations of intracellular concentration and expression levels or fluxes would allow a comprehensive kinetic characterization that is most quickly obtained by dynamic measurements with sufficient perturbation of the system studied 21–23…”
Section: Connection Between Metabolome and Fluxomementioning
confidence: 99%
“…12 C to 13 C isotopomers, we compared the metabolic flow between Hepa1-6 and pancreatic insulinoma (Min6) cell lines (29,30). We previously found that the hepatic glucose transporter 2 (GLUT2) is highly sialylated (unpublished data).…”
Section: Comparison Of Udp-glcnac Metabolism Between Hepatoma and Insmentioning
confidence: 99%